(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. The role of metabolic changes in the anterior eye tissues in the pathogenesis of uveal inflammation in patients with elevated intraocular pressure has been studied poorly. Of particular interest, in this respect, are free radical mechanisms, which can be a trigger of oxidant stress and cause damage to cell membranes in ocular tissues. Purpose. To study the activity of pro-oxidant enzymes and levels of lipid peroxidation products in the uvea tissues in the rabbits with experimental anterior non-infectious uveitis against the background of ocular hypertension. Material and Methods. Forty-one rabbits were divided into 4 study groups. Group 1: 10 animals with experimental ocular hypertension; group 2: 10 animals with experimental allergic uveitis; group 3: 12 animals with ocular hypertension and allergic uveitis; and group 4: 9 intact animals serving as controls. To simulate ocular hypertension in the groups 1 and 3, the animals were made a single 0.1 ml injection of 0.3% carbomer into the anterior chamber. The tissues of the uvea and the aqueous humour were studied biochemically. We estimated the activity of pro-oxidant enzymes, NADPH oxidase and xanthine oxidase, and the content of lipid peroxides: malonic dialdehyde and diene conjugates. The data of the experimental studies were processed using parametric statistical tests with an SPSS package and Statistica 5.5 Results. The activity of pro-oxidants enzymes was increased in all uvea tissues in all study groups; the maximal NADPH oxidase and xanthine oxidase activity was in the animals with both ocular hypertension and uveitis. The NADPH oxidase and xanthine oxidase activity was increased by 51.1% and 63.9% (р<0.001), respectively, as compared with controls. Lipid peroxidation with accumulation of toxic products in the uvea and aqueous humour was noted both in the ocular hypertension-only and uveitis-only groups; however, the maximal values were in an uveitis model against the background of ocular hypertension, where malonic dialdehyde and diene conjugates were increased, respectively, by 67.0% and 54.3% (р<0.001) in the aqueous humour, and, respectively, by 93.1% and 69.1% (р<0.001) in the uvea tissues, compared with controls. Conclusions. Our findings reveal an important link in the pathogenic action of elevated IOP which burdens inflammation in the uveal tissues through the activation of oxidative and peroxidative processes. In addition, our findings support the assumption that primary high-pressure glaucoma can be a factor which worsens inflammation in the anterior eye.